Time-series analysis: variation of anti-acetylcholine receptor antibody titer in myasthenia gravis is related to incidence of Mycoplasma pneumoniae and influenza virus infections. (1st February 2018) - Iwasa, Kazuo; Yoshikawa, Hiroaki; Hamaguchi, Tsuyoshi; Sakai, Kenji; Shinohara-Noguchi, Moeko; Samuraki, Miharu; Takahashi, Kazuya; Yanase, Daisuke; Ono, Kenjiro; Ishida, Chiho; Yoshita, Mitsuhiro; Nakamura, Hiroyuki; et al.
Abstract: Objectives: The exacerbating factors of myasthenia gravis (MG) are unknown. However, it has been speculated that infections may play a role in disease progression. Methods: We calculated the adjusted anti-acetylcholine receptor antibody (Adj-AChR-Ab) titers (range, 0–1) in 58 MG patients between 2006 and 2012. We determined the relationship between Adj-AChR-Ab titer and infection incidence. Results: A cross-correlation function (CCF) analysis of Adj-AChR-Ab titer and incidence of Mycoplasma pneumoniae ( M. pneumoniae ) ( r  = 0.449, P  < 0.0001) and influenza virus ( r  = 0.411, P  < 0.001) infections indicated significant correlations. MG with thymoma was highly correlated with M. pneumoniae infection ( r  = 0.798, P  < 0.0001). The relative risk for Adj-AChR-Ab titer was 1.407 for M. pneumoniae (95% CI, 1.193–1.661 for an increase in one infected patient per monitoring point) and 1.158 for influenza (95% CI, 1.071–1.253 for 100 infected patients). Conclusion: Variation of Adj-AChR-Ab titer is significantly influenced by the presence of M. pneumoniae and influenza virus infections.